KOMPETENSI PEDAGODIK GURU SEKOLAH DASAR PROGRAM PENDIDIKAN PROFESI GURU DALAM PEMBELAJARAN - Wardani, Rizki Putri; Fitriyah, Chumi Zahroul; Ningsih, Yuni Fitriyah (JMIE (Journal of Madrasah Ibtidaiyah Education), 2023)
The purpose of this study was to describe the pedagogical competence of elementary teachers. It includes a planning lesson plan, understanding learning theory until learning evaluation. The research method used was qualitative. The research sample was teachers in the Jember, Banyuwangi, Bondowos, and Jember. Collection of data by an interview with 92 elementary teachers. the sampling technique used purposive sampling. Data analysis was performed by inductive analysis by the result of the interview. The result of this study was pedagogical competency by the elementary teachers. There was seven competence for this study planning a learning plan, determining learning strategy based on characteristics of students, understanding learning theory, understanding learning methods, using, made of evaluations, and reflecting on the learning process. It was almost mastered after joining the teacher certification program But, there were another competence that recah 100%. It needed accompaniment to be a teacher that has pedagogical competence well.